2014
DOI: 10.1523/jneurosci.1280-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dlg5 Regulates Dendritic Spine Formation and Synaptogenesis by Controlling Subcellular N-Cadherin Localization

Abstract: Most excitatory synapses in the mammalian brain are formed on dendritic spines, and spine density has a profound impact on synaptic transmission, integration, and plasticity. Membrane-associated guanylate kinase (MAGUK) proteins are intracellular scaffolding proteins with well established roles in synapse function. However, whether MAGUK proteins are required for the formation of dendritic spines in vivo is unclear. We isolated a novel disc large-5 (Dlg5) allele in mice, Dlg5 LP , which harbors a missense muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…Looking at the Adherens junction, we found that E-Cad level was not affected (n=18) (Fig 6A). Follicle cells also expressed N-Cad, which is integrated in adherens junction, and Dlg5 has been functionally and molecularly linked to this cadherin in mammals [10,12,25]. We therefore looked at N-Cad and spotted an extremely strong and fully penetrant reduction in Dlg5 mutant cells (n>20) (Fig 6B).…”
Section: Dlg5 Is Required For N-cadherin Localization Independently Omentioning
confidence: 99%
“…Looking at the Adherens junction, we found that E-Cad level was not affected (n=18) (Fig 6A). Follicle cells also expressed N-Cad, which is integrated in adherens junction, and Dlg5 has been functionally and molecularly linked to this cadherin in mammals [10,12,25]. We therefore looked at N-Cad and spotted an extremely strong and fully penetrant reduction in Dlg5 mutant cells (n>20) (Fig 6B).…”
Section: Dlg5 Is Required For N-cadherin Localization Independently Omentioning
confidence: 99%
“…CARMA3 has been implicated in facilitating GPCR-induced activation of NFkB via lysophosphatidic acid, endothelin-1, and angiotensin II (Scudiero et al, 2014). Although there does not appear to be any examples of DLG5 in the direct regulation of GPCRs, DLG5 has been implicated in regulating synaptogenesis by enhancing the membrane localization of the transmembrane protein N-cadherin (Wang et al, 2014). DLG5 has also been demonstrated to scaffold atypical protein kinase C (PKC) isoforms, and this provides a mechanism by which DLG5 contributes to the regulation of GPCR-mediated signaling (Nechiporuk et al, 2013).…”
Section: Gpcr-interacting Psd-95 Family Pdz Domain-mentioning
confidence: 99%
“…We showed previously that Dlg5 −/− mice display prominent defects in apical-basal cell polarity and develop brain hydrocephalus, synaptogenesis defects, emphysema-like lungs, and kidney cysts (Nechiporuk et al 2007(Nechiporuk et al , 2013Wang et al 2014). Dlg5 is necessary for the proper maintenance and proliferation of progenitor cells in vivo, and Dlg5 −/− pups and adult mice are correspondingly much smaller than their wild-type littermates.…”
mentioning
confidence: 98%